Drivers of soil heterotrophic respiration in tropical peatlands: a review to inform peat carbon accumulation modelling - Dehaen, Elise M.; Burke, Eleanor J.; Chadburn, Sarah E.; Kaduk, Jörg; Sitch, Stephen; Smith, Noah D.; Gallego-Sala, Angela V. (Frontiers in Geochemistry, 2025)
Globally peatlands store 25% of global soil organic carbon but this large carbon store is at risk under climate change and from widespread anthropogenic disturbances. The impact of climate change on tropical peatlands, which represent 23%–30% of the global peatland area, is particularly poorly understood and Earth System Models do not yet include a suitable representation of the soil carbon cycle for tropical peatlands. Peat decomposition via soil heterotrophic respiration to CO2 (SHR-CO2) is a main component of the peatland carbon cycle. However, the lack of consensus on the importance of different drivers and the scarcity of empirical data hinders model development. Therefore, this study reviews the drivers of SHR-CO2 (moisture, temperature, decomposability and, nutrients and decomposers) for tropical peatlands. We compile available empirical data to inform model development; and highlight priorities for future experimental work that would enable further model refinement. We point out that the sharp decrease of SHR-CO2 under anoxic water-saturated conditions is a major parameter for tropical peat decomposition and the ratio of SHR-CO2 under anoxic conditions to the SHR-CO2 at the optimum moisture is 0.10 ± 0.08. Additionally, we highlight that, at present, the common assumption that SHR-CO2 doubles with an 10°C increase (Q10 of ca. 2) remains the most parsimonious option considering the lack of empirical data to establish a more process-based peatland SHR-CO2 temperature relationship. Finally, we identify three priorities to advance tropical peatland model improvement: (1) narrowing the constraint on the optimum moisture range for SHR-CO2 in tropical peatlands, (2) investigating the interaction between moisture and temperature sensitivity, and (3) identifying the most widely applicable metric to characterise peat decomposability that might enable quantitative comparison across the tropics.